Using of computer game Civilization as stem-project - Shapovalov, Yevhenii; Zhadan, Sergiy; Tarasenko, Roman; Usenko, Stanislav; Shapovalov, Viktor (My University, 2021)
STEM-education nowadays is a trend. One of the ways to provide it is using games. Perspective game to use is Sid Meier's Civilization VI. Previously, it was noted that using of Sid Meier's Civilization VI in education is perspective, but there are no any specific methods to use it. The main advantages of using is Sid Meier's Civilization VI in educational process and method of its usage.
Keywords: кафедра харчової хімії; STEM-approach of education; STEM-підхід в освіті; STEM-project; STEM-проект; computer game Civilization; комп'ютерна гра Civilization; education; освіта; STEM-education; STEM-освіта